Placental Mesenchymal Dysplasia: A Case Report. (5th August 2012) - Agarwal, Rachna; Khatuja, Ritu; Sharma, Lipi; Singh, Alpana
Abstract : Introduction . A rare case of histologically proven placental mesenchymal dysplasia (PMD) with fetal omphalocele in a 22-year-old patient is reported. Material and Methods . Antenatal ultrasound of this patient showed hydropic placenta with a live fetus of 17 weeks period of gestation associated with omphalocele. Cordocentesis detected the diploid karyotype of the fetus. Patient, when prognosticated, choose to terminate the pregnancy in view of high incidence of fetal and placental anomalies. Subsequent histopathological examination of placenta established the diagnosis to be placental mesenchymal dysplasia. Conclusion . On clinical and ultrasonic grounds, suspicion of P.M.D. arises when hydropic placenta with a live fetus presents in second trimester of pregnancy. Cordocentesis can detect the diploid karyotype of the fetus in such cases. As this condition is prognostically better than triploid partial mole, continuation of pregnancy can sometimes be considered after through antenatal screening and patient counseling. However, a definite diagnosis of P.M.D. is made only on placental histology by absence of trophoblast hyperplasia and trophoblastic inclusions.